Strengthening of RC slabs with reinforced concrete overlay on the tensile face - Fernandes, Hugo; Lúcio, Válter; Ramos, António (Engineering structures, 2017)
•Adding concrete overlay on the tensile face increased shear and flexural resistance.•Interface results with reinforcement properly anchored fit well with MC2010.•Ductile behaviour was achieved with reinforcement crossing the interface.•Reinforcement crossing the interface increased bond strength up to 200%. Strengthening of concrete structures with a new concrete layer has been commonly used for columns, beams and slabs. This technique is economic and efficient for structural strengthening since it uses the same base materials, steel and concrete. It is usually applied on the compressed face of the concrete element due to concrete’s recognized behaviour under compression, posing several challenges to control cracking and resistance when applied on the tensile face. For assessing the performance of the strengthening method, twelve slab specimens were designed and tested monotonically. The main parameters to assess in this work were the debonding behaviour and load, and the relationship between the latter and the relative displacements at the interface of the two concrete layers. The performance of the strengthened structures strongly relies on the interaction of the two concrete layers, with this being the main subject of the research about overlaid concrete. The load transfer capacity of the interface depends on the interface shear strength, which in turn is highly dependable on substrate roughness, cleanliness and curing conditions of the newly added layer. Interface performance may be improved by using steel connectors crossing the interface, properly anchored on both layers. The importance for these elements grows as the existing concrete is more deteriorated, since adhesion strength will decrease with lower quality concrete. This paper presents the experimental research for the application of bonded concrete overlays on the tensile face of reinforced concrete slabs, mainly aimed at office buildings and parking facilities, where spatial clearances or inaccessibility to the lower side of the slabs are recurrent. A ductile behaviour upon debonding was achieved for the specimens with reinforcement crossing the interface, and a debonding load up to three times that of the reference specimens without reinforcement crossing the interface.